(untitled) (Perner’s Contacts, 2017)
The article deals with the use of ABC analysis in the inventory management. ABC analysis is a relatively well-known method that is applied in logistics especially in the context of issues of inventory management. The aim of article is to point out to the correct use of ABC analysis, because it is key for effective inventory management.